2013
DOI: 10.1002/etep.1793
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of distributed generation operation modes using new effective voltage stability index in radial system

Abstract: SUMMARY This paper presents detail assessment of the impact of renewable energy type distributed generation operation modes on the voltage stability indices. Most of renewable distributed energy sources are capable of operating in two modes, which are constant voltage and constant power modes. Different simulation results were obtained for voltage stability index (VSI), which serves as indicator of stability. Furthermore, this study has also considered charging station (CS) as a load, that is, gradually increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…However, in real systems, P and Q may flow in opposite directions. In such conditions, the above‐mentioned indicators may not properly evaluate the stability status, which has not considered in research works . To clarify this problem, in the network shown in Figure , the L index is calculated in the following operating points: Case P Load = 600 MW, Q Load = 200 MVAr. In this case, since P and Q are flowing from bus 1 to the other one, bus 1 is considered as the SB.…”
Section: Assessment Of Line Indices Against Different Directions Of Pmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in real systems, P and Q may flow in opposite directions. In such conditions, the above‐mentioned indicators may not properly evaluate the stability status, which has not considered in research works . To clarify this problem, in the network shown in Figure , the L index is calculated in the following operating points: Case P Load = 600 MW, Q Load = 200 MVAr. In this case, since P and Q are flowing from bus 1 to the other one, bus 1 is considered as the SB.…”
Section: Assessment Of Line Indices Against Different Directions Of Pmentioning
confidence: 99%
“…In this regard, these indicators may seem to be a proper tool for voltage stability assessment. Nevertheless, in the sequel, it will be shown that these indices have a major drawback, which is not considered in the literature . To explain this drawback, consider the simple network shown in Figure A, which includes three transmission lines connected in series.…”
Section: Improved Lsz Indicatorsmentioning
confidence: 99%
“…In the following literature, using a two‐bus equivalent circuit, researchers have presented indices such as L mn , L P , line collapse proximity index (LCPI), line voltage stability index (LVSI), simplified voltage stability index (SVSI), power stability index (PSI), L 1, and new voltage stability index (NVSI) based on the bus voltage levels, the maximum transferrable power, and line characteristics. These indices have low computational demand and can easily calculate the stability level of all network buses.…”
Section: Introductionmentioning
confidence: 99%
“…Safety in a power system is usually representative of its capability in maintaining stability against fluctuations and malfunctions . The phenomenon of voltage stability, as one of the restricting factors in power system operation in various sectors including generation, transmission, and distribution, has been received many researchers' and power companies' attention . It is approved that voltage stability can be used as a suitable criterion in order to assess the security level of power systems .…”
Section: Introductionmentioning
confidence: 99%
“…4 The phenomenon of voltage stability, as one of the restricting factors in Nomenclature: Indices: 1, the downstream network of the step-up transformer; 2, the upstream network prior to the step-up transformer Variables and parameters: a, the voltage ratio of the step-up transformer; I L , load current, pu; l, the length of the line, km; p, the real power of load, MW; P, the real power of load, pu; Q, the reactive power of load, pu; R, line resistance, pu; S, load apparent power, pu; V, voltage magnitude at the receiving end of the feeder, pu; V S , voltage magnitude at the sending end of the feeder, pu; X, line reactance, pu; χ, the horizontal axis of xy bidimensional space; Y, the vertical axis of xy bidimensional space; Z, line impedance, pu; φ, the inverse cosine of load power factor; δ, the angle of the line impedance; Δ, the discriminate (delta) of quadratic equation; ΔV, voltage drop across the line; λ, the percentage of the length of the feeder that is located between the sending end and step-up transformer power system operation in various sectors including generation, transmission, and distribution, has been received many researchers' and power companies' attention. [5][6][7][8][9][10] It is approved that voltage stability can be used as a suitable criterion in order to assess the security level of power systems. 1112 claim that power system is a nonlinear dynamic system, and the most important discussion of this system is that of voltage stability.…”
Section: Introductionmentioning
confidence: 99%